Shigella flexneri serotype 1 infections in men who have sex with men in Vancouver, Canada. Issue 3 (March 2015) - Wilmer, A; Romney, MG; Gustafson, R; Sandhu, J; Chu, T; Ng, C; Hoang, L; Champagne, S; Hull, MW
<x xml:space="preserve">Abstract</x> Objectives Outbreaks of shigellosis have been documented in men who have sex with men (MSM), associated with interpersonal transmission and underlying HIV infection. We observed a rise in Shigella flexneri isolates identified in a downtown tertiary‐care hospital laboratory located within the city centre community health area (CHA‐1) of Vancouver, Canada. The objectives of this study were to evaluate clinical outcomes of shigellosis cases among MSM admitted to hospital and to evaluate trends in Shigella cases within Vancouver, Canada. Methods Adult rates of shigellosis were analysed by gender and health region, from 2005 to 2011, followed by retrospective chart review of all hospital laboratory‐identified S. flexneri cases from 2008 to 2012. Serotyping and pulsed‐field gel electrophoresis (PFGE) were performed on these isolates. Results Although shigellosis rates in men within CHA‐1 did not change from 2005 to 2011 (range 33.4–68.5 per 100 000; P = 0.74), they were significantly higher than in other regions within the city of Vancouver (P ≤ 0.001) and the province of British Columbia (P ≤ 0.001). Shigella flexneri rates in men within CHA‐1 increased significantly (range 2.3–51.4 per 100 000; P < 0.001), starting in 2008, and were higher than in other regions within Vancouver (P ≤ 0.01). Seventy‐nine isolates of S. flexneri from 72 patients were identified by a single hospital laboratory. All patients were male and predominantly MSM (91.7%) and HIV‐infected (86.1%), with most (92.6%) demonstrating CD4 counts ≥ 200 cells/μL. In total, 38.0% required hospitalization. Most (87.3%) had S. flexneri serotype 1 infection, with 72.9% of these representing a single PFGE pattern. Conclusions We identified high levels of transmission of a primarily clonal strain of S. flexneri serotype 1 in our local MSM population, resulting in a substantial burden of illness and health care resource use secondary to hospital admissions.